Shorter sleep duration is associated with lower GABA levels in the anterior cingulate cortex - Park, Shinwon (Sleep Med, 2020)
BACKGROUND: Alterations in the levels of gamma-aminobutyric acid (GABA) and glutamate+glutamine (Glx), which are major inhibitory and excitatory neurotransmitters, respectively, are frequently associated with insomnia. Previous reports also suggested the involvement of the anterior cingulate cortex (ACC) and medial prefrontal cortex (mPFC) in insomnia and shorter sleep duration. In the current study, we investigated whether the GABA and Glx levels were altered in the ACC/mPFC in subclinical insomnia while focusing on the sleep duration. METHODS: We examined levels of GABA and Glx in the ACC/mPFC of the brain with magnetic resonance spectroscopy in 166 individuals with subjective sleep complaints but without a diagnosis of insomnia. Participants were divided into two groups according to sleep duration (≥ 6 hours/night: n=79 vs. < 6 hours/night: n=74), which was measured using a wrist-worn actigraphy. Working memory function and overall subjective sleep quality were assessed with a computerized neuropsychological test and self-report questionnaire, respectively. RESULTS: GABA levels in the ACC/mPFC were lower in the shorter sleep duration group relative to the longer sleep duration group (t=−2.21, p=0.03). Glx levels did not differ between the two groups (t=−0.20, p=0.84). Lower GABA levels were associated with lower spatial working memory performance in the shorter sleep duration group (β=−0.21, p=0.03), but not the longer sleep duration group (β=0.04, p=0.72). CONCLUSION: Shorter sleep duration was associated with lower GABA levels in the ACC/mPFC. These findings may provide insight into the underlying mechanisms of impaired working memory function related to insomnia and sleep loss.